2019
DOI: 10.1002/pat.4674
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DOPO‐based pyrazine derivative and its effect on flame retardancy and thermal stability of epoxy resin

Abstract: A novel DOPO-based pyrazine derivative 6-((2-hydroxyphenyl)(pyrazin-2-ylamino) methyl)dibenzo[c,e][1,2]oxaphosphinine 6-oxide (DHBAP) was triumphantly synthesized by a two-step addition reaction using 2-aminopyrazine, 2hydroxybenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) as reactants, and characterized by Fourier-transform infrared (FTIR), 31 P nuclear magnetic resonance (NMR) and 1 H NMR. Afterwards, the addition type flame retardant (DHBAP) was utilized to modify epoxy resin (EP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…As shown in Figure 2A, the multi-peaks at 10 to 10. existence of chiral carbon atoms. 33 The above NMR results further confirmed that the target product DHI was successfully synthesized.…”
Section: Measurementssupporting
confidence: 64%
See 1 more Smart Citation
“…As shown in Figure 2A, the multi-peaks at 10 to 10. existence of chiral carbon atoms. 33 The above NMR results further confirmed that the target product DHI was successfully synthesized.…”
Section: Measurementssupporting
confidence: 64%
“…According to the literature, the synergistic systems such as DOPO/maleimide, 23,24 DOPO/silsesquioxane, [25][26][27] DOPO/ cyclotriphosphazene 28,29 and DOPO/triazine, [30][31][32] Figure 1 showed IR spectra of DOPO and DHI. As to DOPO, the characteristic peak at 2436 cm −1 was attributed to P-H bond, 33 which was observed to disappear significantly for DHI, indicating DOPO had successfully participated in reaction. Moreover, the peaks at 3435, 3300, 1685 and 1477 cm −1 were attributed to -OH, N-H bond, imidazoline ring and benzene ring, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 HNMR, 11 B NMR, and 31 P NMR of DTPA and AZB were recorded using a Bruker AVANCE AV II-400 NMR instrument, and using DMSO-d 6 as a solvent.…”
Section: Characterizationmentioning
confidence: 99%
“…It is well known that 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) derivatives display superior flame retardant properties as consequence of activity in both the gaseous and condensed phases. [11][12][13][14] Many DOPO-based flame retardants with excellent flammability inhibiting properties have been reported. [15][16][17][18][19][20] A flame retardant derived from DOPO and triazole has been prepared.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback of EP/7.5APP/ 2.5BPOPA thermoset was its lack of transparency. Other low‐flammability EPs also showed low transparency or no transparency, for example, chitosan‐based DOPO derivatives synthesized by Liu et al and pyrazine‐based DOPO derivative synthesized by Tang et al . The utilization of these materials would be limited by their lacks of transparency and aesthetics .…”
Section: Introductionmentioning
confidence: 99%